Prenatal linguistic exposure shapes language brain responses at birth - Andréanne René; Laura Caron-Desrochers; Julie Tremblay; Phetsamone Vannasing; Kassandra Roger; Solène Fourdain; Laurence Petitpas; Catherine Taillefer; Isabelle Boucoiran; Judit Gervain; Natacha Paquette; Anne Gallagher (Communications Biology)
Abstract Newborns have an immature brain network responsible for speech processing that resembles the adult language network. However, it remains unclear how prenatal experience modulates this network. To test this, we exposed 39 fetuses to a story in their native language and in a foreign language during the last month of gestation, while another group of 21 fetuses received no experimental prenatal exposure. Within 3 days of life, neonates’ brain responses were recorded using functional near-infrared spectroscopy (fNIRS) whilst they listened to the same story in their native language and in two foreign languages, one of which neonates had been prenatally exposed to. Results revealed that brain responses to the native language and the prenatally exposed foreign language were similar, whereas they differed in the left temporal and right prefrontal regions when listening to a prenatally unexposed foreign language. Findings indicate that foetuses’ linguistic environment influences speech processing at birth.